A Concise Synthesis of Mupirocin H Using a Cross‐Metathesis‐Based Strategy. Issue 23 (11th July 2014) - Sengupta, Sandip; Sim, Taebo
Abstract: A highly efficient (10.1 % overall yield) and convergent (longest linear sequence of 16 steps) synthesis of mupirocin H has been achieved, starting from commercially available (+)‐( R )‐Roche ester. The route relies on an efficient Grubbs cross‐metathesis reaction to generate a key, late‐stage E ‐olefin intermediate, and a cobalt‐catalysed diastereoselective Reformatsky reaction to produce a β‐hydroxy ester that serves as a late‐stage intermediate. Abstract : A highly efficient (10.1 % overall yield) and convergent (longest linear sequence of 16 steps) synthesis of mupirocin H is described, starting from commercially available (+)‐( R )‐Roche ester.